2017
DOI: 10.1590/s0100-736x2017001000014
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização clínica e histopatológica de bulbos oculares de cães e gatos (2005-2015)

Abstract: RESUMO: Objetivou-se realizar a caracterização clínica e histopatológica de bulbos oculares de cães e gatos, removidos cirurgicamente por indicação clínica, no período entre 2005-2015. Foram realizados 101 procedimentos de remoção do bulbo ocular, 93 enucleações (92%) e 8 exenterações (8%). Os procedimentos foram realizados em 80 cães, (79% dos casos) e em 21 gatos (21% dos casos). Os cães submetidos à intervenção cirúrgica apresentavam perfurações oculares (n=31, 39%), glaucoma (n=19, 24%), protrusão ocular (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…The differential diagnosis of microphthalmia was ruled out, as ultrasound and histopathological exams demonstrated that there was no evidence of the ocular bulb, and the alteration of microphthalmia is characterized by defective development of the primary vitreous, that is, clinically the patient has an underdeveloped and small eye. Because it is so small, reaching the point of being imperceptible to the naked eye, it can be confused with anophthalmia [4,14]. This condition differs from anophthalmia, which is characterized by the absence of all ocular tissues [5,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis of microphthalmia was ruled out, as ultrasound and histopathological exams demonstrated that there was no evidence of the ocular bulb, and the alteration of microphthalmia is characterized by defective development of the primary vitreous, that is, clinically the patient has an underdeveloped and small eye. Because it is so small, reaching the point of being imperceptible to the naked eye, it can be confused with anophthalmia [4,14]. This condition differs from anophthalmia, which is characterized by the absence of all ocular tissues [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…This condition is characterized by a failure in growth, by the invagination of the optic cup, or even by defective development of the primary vitreous. Clinically, the individual has an underdeveloped eye, being so small and imperceptible to the naked eye, that it can be confused with anophthalmia and, for this reason, the microscopic evaluation of the orbital tissue for identification must be performed [4]. The aim of this study was to report a case of bilateral anophthalmia in a domestic cat.…”
Section: Introductionmentioning
confidence: 99%
“…The results were as expected and according to the existing literature, which demonstrates that these are the most common eye diseases that lead to irreversible blindness found in small animal ophthalmology practice. [28][29][30][31][32][33][34] Other diseases or conditions were also cited in the survey (table 2). Some of these diseases are interesting in the medical sense, but not very common in the ophthalmology practice, such as central blindness.…”
Section: Discussionmentioning
confidence: 99%
“…O uso da dorzolamida a 2% é preconizado no tratamento dos glaucomas secundários [23]. Possui relevância especial na medicina veterinária devido o glaucoma secundário ser o mais prevalente em cães e gatos [9,27].…”
Section: Discussionunclassified